The Pentateuch : history or story? - Cox, Howard H., 1924- (Lanham, Md. : University Press of America, 2005)
"This book assumes questions that perceptive readers of all persuasions might ask about the Bible. These questions pertain both to the nature of the text and the text itself. With regard to the former, its historical development is described in reverse order, back through 16th century England to the definitive Hebrew text from which all modern translations are made, the Leningrad Codex, dated 1008 CE. The development continues through prior centuries, importantly, to the Dead Sea Scrolls, which raise new questions about which text to translate."--BOOK JACKET.
Ch. 1. Which Bible? -- Ch. 2. Genesis -- Ch. 3. Exodus, Leviticus, Numbers -- Ch. 4. Deuteronomy -- Ch. 5. Biblical or not?
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; Narration in the Bible